Effectiveness of promoting the healing process of diabetic ulcers with curcumin gauzes in Lopburi Province - Sribular, Pramuan; Nuysri, Mukda; lemsawasdikul, Warinee (Thai Journal of Nursing, 2024)
The purpose of this quasi-experimental research was to study the effectiveness of promoting the healing process of diabetic ulcers (DU) with curcumin gauzes in Lopburi Province. A group of 64 diabetic patients with DU was purposively selected from Pattananikom Community Hospital to be an experimental group and from Thaluang Community Hospital to be a comparison group, 31 person in each group. The research tools were promoting the healing process of DU with curcumin gauzes, and the severity of open wound assessment form (OWAF). The content validity index and interrater reliability coefficient of OWAF were equal to 0.93. Data were analyzed by descriptive statistics, Chi-square test, Independent t-test, Proportional test, and Mann-Whitney U test. The results revealed as follows. 1) After 4 weeks, the experimental group had significantly higher healing rate of DU compared to the comparison group, and DU had healed significantly faster than the comparison group (p <.001). 2) In the 2nd, 3rd, and 4th week, the experimental group had significantly lower mean score of wound severity compared to the comparison group (p < .01). 3) The experimental group had mean rates of decrease in width, length, depth of DU per week and decrease in DU circumference per week that were significantly greater than the comparison group, and mean of wound contraction per week that was significantly more than the comparison group (p <.001). Finally, 4) The mean material cost in wound dressing of the experimental group was significantly less than the comparison group (p <.001).